1994
DOI: 10.1002/eji.1830241032
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor‐induced Fas ligand expression in cytotoxic T lymphocyte clones is blocked by protein tyrosine kinase inhibitors and cyclosporin A

Abstract: Fas/APO-1 is a member of the tumor necrosis factor receptor family of proteins that induces apoptosis when cross-linked with monoclonal antibody (mAb) or with its physiological ligand. Recently, both a perforin-based and a Fas-based mechanism have been proposed to account for T cell-mediated cytotoxicity. In the present study we used a murine CD8+ cytotoxic T lymphocyte (CTL) clone (KB5 C20) specific for H-2Kb and a T cell receptor (TcR)-negative variant of the same clone (2005-D4) to test (i) whether the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(118 citation statements)
references
References 52 publications
10
106
0
2
Order By: Relevance
“…This indicates that degranulation of preformed FasL occurs in response to both TCR stimulation and to stimulation with PMA. In agreement with this finding we observed that anti-CD3 stimulation induced FasL transcription, which was blocked by CsA 13,14 whereas PMA failed to do so (Figure 2d). …”
Section: Resultssupporting
confidence: 89%
“…This indicates that degranulation of preformed FasL occurs in response to both TCR stimulation and to stimulation with PMA. In agreement with this finding we observed that anti-CD3 stimulation induced FasL transcription, which was blocked by CsA 13,14 whereas PMA failed to do so (Figure 2d). …”
Section: Resultssupporting
confidence: 89%
“…The former is likely, because it has been shown that the expression of FasL transcripts is induced by T cell receptor engagement. 14 In addition, an increase in the percentage of CD8 + cells which express FasL in patients with aGVHD has been demonstrated. 15 The relationship between the Fas/FasL system and the development of aGVHD is complex.…”
Section: Discussionmentioning
confidence: 99%
“…[136][137][138] Both of these types of kinases are important in T cell activation. [136][137][138][139] Consistent with this observation, Fas-L is expressed following activation of the TCR leading to the phosphorylation of these kinases and expression is inhibited by cell treatment with immunosuppressive drugs. 139 Ras signaling has also been implicated in tyrosine kinase activation and hence both the Ras and Lck pathways may contribute to the up-regulation of Fas-L transcription.…”
Section: Nefmentioning
confidence: 78%
“…[136][137][138][139] Consistent with this observation, Fas-L is expressed following activation of the TCR leading to the phosphorylation of these kinases and expression is inhibited by cell treatment with immunosuppressive drugs. 139 Ras signaling has also been implicated in tyrosine kinase activation and hence both the Ras and Lck pathways may contribute to the up-regulation of Fas-L transcription. 140 Therefore, HIV infection may activate tyrosine kinases (via Nef) that converge in a common activation pathway leading to Fas/Fas-L interaction and the induction of apoptosis.…”
Section: Nefmentioning
confidence: 78%